Uniform deformation design of outrigger braced skyscrapers: A simplified method for the preliminary design stage. (June 2021) - Alavi, Arsalan; Mele, Elena; Rahgozar, Reza; Noroozinejad Farsangi, Ehsan; Takewaki, Izuru; Málaga-Chuquitaype, Christian
Abstract: A stiffness-based method for the preliminary design of outrigger braced skyscrapers is proposed. The method is founded on the concept of uniform distribution of deformation. This approach originates from the minimum-compliance optimization, in which the stiffest layout for the structure is sought for a given amount of material. Design variables include: the flexural stiffness of the core structure, the outrigger-belt elevation, and the peripheral column dimensions. These parameters are specified by requiring the curvature to be kept constant, yet minimum, as long as the allowable stress and displacement constraints are imposed. The resulting procedure is presented through a simplified hand-calculation algorithmic framework, which may be used during the preliminary design stage to estimate the size of elements and to give an initial assessment of the structural behavior. In order to show the practical application of the proposed method, a structure equipped with one outrigger is designed using the proposed algorithm. The comparative analysis of the results reveals that the presented method provides a rather high degree of accuracy in practice.